International-Cultural Communication of the Saman Dance Performance by Indonesian Students in Nanjing - Dani Fadillah; Zalik Nuryana; Muhammad Sahuddin; Dong Hao (International Journal of Visual and Performing Arts, 2019)
This study aims to find out how Indonesian students in China can become ambassadors to introduce and promote Indonesian names in a cultural frame. Saman dance, which is a typical dance of the people of Aceh, can be performed well by Indonesian students even though, on average, those who become dancers are not Aceh residents. This research is field research, where the author follows and observes Indonesian students while they are performing Saman. The results of this study show that foreign nationals abroad welcomed the saman dance performed by Indonesian students in China.